Simulation of Dural Repair in Minimally Invasive Spine Surgery With the Use of a Perfusion-Based Cadaveric Model. Issue 6 (29th March 2019) - Buchanan, Ian A; Min, Elliot; Pham, Martin H; Donoho, Daniel A; Bakhsheshian, Joshua; Minneti, Michael; Zada, Gabriel; Giannotta, Steven L; Hsieh, Patrick C; Liu, John C
Abstract: BACKGROUND AND IMPORTANCE: In an era of curtailed work hours and concerns over achieving technical proficiency in the repertoire of procedures necessary for independent practice, many residencies have turned to model simulation as an educational adjunct. Cerebrospinal fluid (CSF) leak repair after inadvertent durotomy in spine surgery is a fundamental skillset for any spine surgeon. While primary closure with suture is not always necessary for small durotomies, larger defects, on the other hand, must be repaired. However, the dire consequences of inadequate repair dictate that it is generally performed by the most experienced surgeon. Few intraoperative opportunities, therefore, exist for CSF leak repair by trainees. OBJECTIVE: To simulate dural repair in spine surgery using minimal-access techniques. METHODS: A cohort of 8 neurosurgery residents was evaluated on their durotomy repair efforts in a perfusion-based cadaveric model. RESULTS: Study participants demonstrated consistent improvement across trials, with a significant reduction in closure times between their initial (12 min, 7 sec ± 4 min, 43 sec) and final attempts (7 min, 4 sec ± 2 min, 6 sec; P  = .02). Moreover, all trainees—irrespective of postgraduate year—were able to accomplish robust dural closures resistant to simulated Valsalva maneuvers. Participants reported high degrees of model realism and exhibited significant increases in postprocedure confidence scores. CONCLUSION: Our results support use of perfusion-based simulation models as a complement to neurosurgery training, as it affords unrestricted opportunities for honing psychomotor skillsets when resident learning is increasingly being challenged by work-hour limitations and stricter oversight in the context of value-based healthcare.